Classroom experiments: Teaching specific topics or promoting the economic way of thinking?. Issue 4 (1st October 2016) - Emerson, Tisha L. N.; English, Linda K.
ABSTRACT: The authors' data contain inter- and intra-class variations in experiments to which students in a principles of microeconomics course were exposed. These variations allowed the estimation of the effect on student achievement from the experimental treatment generally, as well as effects associated with participation in specific experiments. The authors find that students exposed to the experimental treatment enjoyed significantly higher positive learning gains than those in the no-experiment control group. The productivity experiment was associated with significantly more positive learning, the minimum wage experiment with less negative learning, and the externality experiment with less positive learning. The authors further find that some experiments affect student learning on the demonstrated topics, while others affect student learning on unrelated topics.